The expression of DLGAP5 associate with progression and prognosis in glioma - Kangjie Du; Yu Zhang; Mengyao He; Yalin Lu; Xingjie Chen; Hao Yu; Qiang Huang (Annals of Molecular and Genetic Medicine - Peertechz Publications, 2022)
Glioma is the most common primary malignant tumor of the central nervous system and is related to poor clinical outcomes. At present, the standard treatment of glioma in clinical practice is to maximally remove the focus on the premise of protecting the neurological function, supplemented by postoperative chemotherapy and radiotherapy. However, after standard treatment, the prognosis of glioma patients is still not satisfactory. DLGAP5 has been shown to play an important role in the occurrence and progression of various tumors. This study examined the expression of DLGAP5 in glioma samples and its significance in predicting the prognosis of glioma patients. TCGA and CGGA datasets were used to explore the difference in DLGAP5 expression between glioma and normal central nervous system tissues and to investigate the prognostic value of DLGAP5 expression in glioma patients. The cBioPortal online analysis website was used to explore the gene mutations of DLGAP5 expressing in glioma. The String database and GEPIA online analysis website were used to perform Enrichment Analysis to explore the molecular mechanism of DLGAP5.In this study, we observed that DLGAP5 expression was upregulated in glioma tissues compared with normal CNS tissues and was negatively associated with the prognosis of glioma patients. DLGAP5 may affect the occurrence and progression of glioma mainly through gene mutation, gene amplification, and gene depth deletion. At the same time, the molecular inhibition of DLGAP5 may be related to the cell cycle and the p53 pathway. In conclusion, our findings suggested that DLGAP5 may be a therapeutic target and an independent prognostic indicator for glioma.